Simulation and reproduction of a manipulator according to classical arm representation and trajectory planning - Bani Hashim, Ahmad Yusairi; Shukor, Ahmad Zaki; Shamsuddin, Syamimi; Kamsani, Silah Hayati; Mat Ali, Mahasan (ASTES Publishers, 2019)
The technical and vocational institutions are the key feeders for skilled human capital in the robotic revolution economy. It is essential to engage the students by creating new, affordable robotics at a fraction of the cost. This study presents the design and simulation of a six-axis robot manipulator specifically made for education and training. The robot was developed based on Chriss-Annin’s configuration. The robot arm was printed using Fused Deposition Modelling technique using the acrylonitrile butadiene styrene filament. Before it was constructed, the arm parameters were assessed using Scilab as the tool and the Ntraditional and fundamental methods: the Denevit-Hartenberg representation, the forward kinematics, the inverse kinematics, and the trajectory planning. The outcomes showed that the arm was working well on positioning and path planning. Therefore, the complete assembly of the robot should be able to assume a role in education and training. This work is an extension of the paper entitled “Lightweight Robot Manipulator for TVET Training using FDM Technique” published in 2018 Symposium on Electrical, Mechatronics and Applied Science 2018 (SEMA 2018).